MATHEMATICAL DESCRIPTION OF THE CHANGE IN THE ATMOSPHERIC TEMPERATURE DURING DAYS AND NIGHTS (Innovation in Woodworking Industry and Engineering design, 2026)
A mathematical description of the periodically changing during many days and nights temperature of the atmospheric air as a processing medium has been suggested. It is introduced in the boundary conditions of our own mutually connected 2D non-linear mathematical models of the logs’ freezing and defrosting processes. For the numerical solving of the models a software program has been prepared in the calculation environment of Visual Fortran Professional. Results from a simulative investigation of the 2D non-stationary temperature distribution in beech logs with a diameter of 0.24 m, length of 0.48 m, moisture content of 0.6 kg·kg-1, and initial temperature of 0 oC during their 5 days and nights continuous freezing and defrosting at sinusoidal change of the air temperature with initial values of –5 oC and different amplitudes are presented and analyzed.